New techniques for sentinel node biopsy in breast cancer - Ferrucci, M; Franceschini, G; Douek, M (AME Publishing Company, 2018)
Sentinel lymph node biopsy (SLNB) is still the standard of care for axillary nodal staging in patients with invasive breast cancer (BC) and clinically negative lymph nodes (LNs). It successfully replaced the more invasive and morbid axillary lymph node dissection (ALND). The actual standard for SLNB is the radioisotope (RI) with or without blue dye (BD) technique. Because of several drawbacks reported in worldwide experiences, new techniques have been developed in the last years: indocyanine green (ICG) fluorescence, superparamagnetic iron oxide (SPIO) nanoparticles and contrast-enhanced ultrasound (CEUS) using microbubbles. Whilst each technique has its own advantages/disadvantages they are increasing their efficacy and are candidate to represent a new standard for SLNB in next future. This is a comprehensive review of current limitations of conventional techniques besides the improvements and innovations of new methods which, anyway, need future randomized controlled trials to be fully validated.